2017
DOI: 10.1038/s41598-017-06061-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 mediates arsenic trioxide resistance by activating Nrf2 and suppressing apoptosis in lung cancer cells

Abstract: Arsenic trioxide (ATO) resistance is a challenging problem in chemotherapy. However, the underlying mechanisms remain to be elucidated. In this study, we identified a high level of expression of miR-155 in a human lung adenocarcinoma A549R cell line that is highly resistant to ATO. We showed that the high level of miR-155 was associated with increased levels of cell survival, colony formation, cell migration and decreased cellular apoptosis, and this was mediated by high levels of Nrf2, NAD(P)H quinone oxidore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…As mentioned earlier; one of the difficulties faced in chemotherapy is the development of resistance to chemotherapeutic agents (Li et al, 2008). It appears that miR-155 is involved in the resistance of tumor cells into ATO (Gu et al , 2017). It has been shown that miR-155 makes lung cancer cells resistant to ATO by the activation of the Nrf2 signaling pathway.…”
Section: Mir-155mentioning
confidence: 99%
“…As mentioned earlier; one of the difficulties faced in chemotherapy is the development of resistance to chemotherapeutic agents (Li et al, 2008). It appears that miR-155 is involved in the resistance of tumor cells into ATO (Gu et al , 2017). It has been shown that miR-155 makes lung cancer cells resistant to ATO by the activation of the Nrf2 signaling pathway.…”
Section: Mir-155mentioning
confidence: 99%
“…The interaction between tRNAs and ferroptosis includes two possible manners. First, tRNAs are required in the synthesis of ferroptosis associated factors such as SLC7A11, GPX4, and IREB2, thus the mutation of tRNAs may alter the expression of these factors and then influence ferroptosis 217 . Second, tRNAs have multiple interaction partners including aminoacyl-tRNA-synthetases, mRNAs, ribosomes and translation factors 159 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the involvement of miRNAs in regulating HO-1 in cancer cells has been proved. In particular, miR-155 favors lung cancer resistance to arsenic trioxide through Nrf2/HO-1 activation [ 78 ]. miR200a, in breast cancer, regulates HO-1 via Nrf2 activation by targeting Keap1 mRNA [ 79 ].…”
Section: Ho-1 Gene Transcription and Protein Localizationmentioning
confidence: 99%